Genetic improvement in tobacco crops. Molecular mechanisms and regulation - Menéndez Álvarez, Eduardo (2020)
Diseases produced by phytopathogenic fungi are one of the main causes of crop loss since humans started growing plants. Until now, these diseases have been mainly controlled by the improvement of plant resistance by means of selection and crossbreeding programs, the use of agrochemical products and an accurate crop rotation. Nevertheless, these strategies are not enough to control diseases caused by fungi because of the necessary long periods of time to carry out the crossbreeding and backcrossing as well as the selection of commercial varieties, which is plenty of time for new fungi types with different levels of virulence to appear. On the other hand, the use of agrochemical products is expensive and these eventually lack efficacy as a result of the evolution of the pathogen, apart from being extremely dangerous to the ecosystem. Implementing modern techniques of plant biotechnology as well as genetic engineering makes possible the obtainment of plants that protect themselves against fungi or fungal groups in short time. Tobacco is studied as a model to understand the molecular mechanisms of transference and regulation, which could be applied to crops of high economic importance such as the potato